Parameters calculation of 5 HP AC induction motor - Ismail, Daut; Karem, Anayet; Muhammad Irwanto; N. Gomesh; M. Muzhar; M. Asri; Syatirah (Universiti Malaysia Perlis, 2009)
Organized by School of Mechatronic Engineering (UniMAP) & co-organized by The Institution of Engineering Malaysia (IEM), 11th - 13th October 2009 at Batu Feringhi, Penang, Malaysia.